Profiles of Textile Production in a Regional Space: Conchucos, Ancash, Perú, between 1593 and 1876 - Chocano, Magdalena (2016)
There is a good deal of data to suggest that the corregimiento of Conchucos was a significant textile production center. The systematization of this data has allowed us to map out the geography of the textile economy in the area, highlighting those zones where the work was carried out. On the other hand, although the lack of series for the textile production of Conchucos precludes a study of this sector that is comparable with that of Huamanga or Cusco, the available demographic information for the corregimiento allows the long-term evolution of its textile economy to be traced through to the eventual division into provinces during the Republican era. This analysis allows the ethnic and gender distribution of work in the textile sector to be discerned, while elucidating some of the elements of economic change that affected this territory.